CNDs@zeolite: new room-temperature phosphorescent materials derived by pyrolysis of organo-templated zeolites. Issue 41 (17th October 2017) - Mu, Y.; Shi, H.; Wang, Y.; Ding, H.; Li, J.
Abstract : CNDs@zeolite composites with long-lived room-temperature phosphorescence have been prepared by pyrolysis of organic templates confined in zeolites. Abstract : Room-temperature phosphorescent (RTP) materials, typically heavy metals containing inorganic/metal complexes and a few pure organics, are highly desired in optoelectronics, biological imaging, and anti-counterfeit fields. In this study, we discovered a new class, CNDs@zeolite, of RTP materials prepared by the pyrolysis of organic amines confined in zeolites. The resulting composite materials exhibit a long lifetime of hundreds of milliseconds and high quantum yields of up to ca. 18%. The RTP properties can be modulated by selecting different organic templates and zeolitic frameworks.